GAZ AND GAS CONDENSATE WORK AND PREPARATION SYSTEMS METHODS OF USE ANALYSIS - Abdirazakov Akmal Ibrahimovich; Namozov is the son of Ogabek Mahmud (Ta’lim innovatsiyasi va integratsiyasi, 2026)
ANNOTATION One of the most important components of the country’s gas industry development strategy is the State Program for the Creation of a Unified System of Gas Production, Transportation and Supply in 2007. Solving the problems of effective gas pipeline management includes a set of tasks for modeling and optimal planning of the operating modes of the entire chain of gas pipeline technological facilities. The solution to these problems is based on the integration of models of facilities managed by the gas production company, from wells to the compression compressor station (SCS). Currently, there is a significant gap between the capabilities of modern gas production, gathering and processing modeling systems, such as PIPESIM, OLGA (Schlumberger) and others, and the needs of subsoil users to solve problems of modeling and controlling the operating modes of objects that perform these processes as a single system. These gaps are mainly due to the lack of mathematical models and algorithms for modeling stable and unstable operating modes of the entire gas production organization, which usually includes wells, gas well networks, field gas gathering networks (GFG), gas primary treatment facilities (GPTP), inter-field gas gathering collectors (IGGC), integrated gas complex treatment facilities (IGCP), compression compressor stations (SCS) and main gas pipelines (MGP). Thus , the development of mathematical methods and algorithms that solve the technological problems of modeling and management of gas production complex regimes is currently an urgent task.